2012
DOI: 10.1590/s1808-16572012000200013
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de isolados de Metarhizium anisopliae (Metsch.) Sorok. (Deuteromycotina: Hyphomycetes) para o controle de Mahanarva fimbriolata (Stal, 1854) (Hemiptera: Cercopidae) em cana-de-açúcar

Abstract: RESUMOO objetivo desta pesquisa foi selecionar isolados de Metarhizium anisopliae (Metsch.) Sorok. (Deuteromycotina: Hyphomycetes) patogênicos para a cigarrinha da raiz Mahanarva fimbriolata. O estudo foi feito em condições de laboratório, utilizando-se exemplares de ninfas de cigarrinha da raiz que, após serem cuidadosamente separadas por tamanho em grupos de 10 indivíduos, foram inoculadas com suspensões de conídios da ordem de 1,0 x 10 7 ; 0,5 x 10 8 ; 1,0 x 10 8 ; 0,5 x 10 9 e 1,0 x 10 9 ; conídios/mL para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
0
0
3
Order By: Relevance
“…Regarding efficacy in the control of nymphs, Kassab et al (2012) observed that isolations of M. anisopliae (BIO 08 and IBCB 425) showed an efficacy between 73.33 and 70.6% in the control of M. fimbriolata, 15 days after application, results similar to those obtained in this study with the T1 isolations: MT-51 (01) and T2: P-50 (01), this tendency may be influenced by the high capacity of infection of M. anisopliae (Freitas et al, 2012). This was shown previously by Barbosa et al (2011) when evaluating the efficacy of M. anisopliae isolations, found an efficiency of 83% in the control of nymphs of M. fimbriolata.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding efficacy in the control of nymphs, Kassab et al (2012) observed that isolations of M. anisopliae (BIO 08 and IBCB 425) showed an efficacy between 73.33 and 70.6% in the control of M. fimbriolata, 15 days after application, results similar to those obtained in this study with the T1 isolations: MT-51 (01) and T2: P-50 (01), this tendency may be influenced by the high capacity of infection of M. anisopliae (Freitas et al, 2012). This was shown previously by Barbosa et al (2011) when evaluating the efficacy of M. anisopliae isolations, found an efficiency of 83% in the control of nymphs of M. fimbriolata.…”
Section: Discussionsupporting
confidence: 87%
“…Se utilizaron ninfas de M. andigena de 8 y 10 mm de longitud, provenientes de un cultivo de caña de azúcar cultivar POJ 93, de la finca La Julita, parroquia Teniente Hugo Ortiz, del cantón Pastaza, sin aplicación de productos químicos. Las unidades de observación estaban constituidas por una caja Petri (100 × 15 mm) que contenía una hoja de caña de 8 cm de longitud, lavada con agua destilada estéril y envuelta por los extremos en un fragmento de algodón humedecido con agua; sobre la hoja se colocaron diez ninfas de M. andigena (Freitas et al, 2012).…”
Section: Evaluación De Patogenicidadunclassified
“…Los conidios se contaron en una cámara de Neubauer y las suspensiones se prepararon mediante dilución, de acuerdo a Gürlek et al (2018). Se utilizó una concentración de 1×10 8 conidios/mL de cada aislado; en cada placa de Petri se aplicó 1 mL de suspensión sobre las ninfas con una micropipeta manual de volumen variable de 100 a 1000 µL (Boeco, Alemania), de acuerdo con Freitas et al (2012).…”
Section: Evaluación De Patogenicidadunclassified
“…As metodologias utilizadas em bioensaios em laboratório com aplicação de fungos entomopatogênicos sobre ninfas de M. fimbriolata resultaram em alta mortalidade da testemunha especialmente quando as ninfas foram colocadas para se alimentar de folhas, com valores de mortalidade na testemunha entre 78 e 96% (FREITAS et al 2012) ou entre 50 e 90%, após seis dias (LOUREIRO et al, 2005), o que torna questionável as conclusões destes estudos. Algumas espécies de insetos são mais delicadas e não toleram manipulação e o stress durante o bioensaio acaba mascarando a ação do fungo, e comprometendo a qualidade do teste.…”
Section: Introductionunclassified